2001
DOI: 10.1016/s0014-5793(01)02097-x
|View full text |Cite
|
Sign up to set email alerts
|

Syk protein‐tyrosine kinase is involved in neuron‐like differentiation of embryonal carcinoma P19 cells

Abstract: Syk has been implicated in activated immunoreceptors to downstream signaling events in hematopoietic cells. Here we report that Syk is expressed in neuron-like cells and involved in neuron-like differentiation of embryonal carcinoma P19 cells. Immunoblot, RT-PCR, and Northern analysis indicated that Syk is expressed in mouse brain, PC12 and P19 cells. In addition, Syk was found to be tyrosine phosphorylated during neuron-like differentiation of P19 cells. Furthermore, adenovirus-mediated overexpression of Syk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…In agreement with this, we found that CD3 recruitment by a CD3 antibody induced an elevation of [Ca 2ϩ ] i in cultured neurons. The expression of ZAP-70 -related tyrosine kinase in developing neurons (Ishijima et al, 1995;Yoneya et al, 1998), and the reported role of Syk in neurite outgrowth (Tsujimura et al, 2001;Gallagher et al, 2007) is compatible with the notion that Syk/ZAP-70 could be a relevant component of the intracellular transduction pathway connecting CD3 activation and Ca 2ϩ mobilization to negatively control dendritic shaping.…”
Section: Potential Mechanisms For Cd3 Neuronal Functionsupporting
confidence: 78%
“…In agreement with this, we found that CD3 recruitment by a CD3 antibody induced an elevation of [Ca 2ϩ ] i in cultured neurons. The expression of ZAP-70 -related tyrosine kinase in developing neurons (Ishijima et al, 1995;Yoneya et al, 1998), and the reported role of Syk in neurite outgrowth (Tsujimura et al, 2001;Gallagher et al, 2007) is compatible with the notion that Syk/ZAP-70 could be a relevant component of the intracellular transduction pathway connecting CD3 activation and Ca 2ϩ mobilization to negatively control dendritic shaping.…”
Section: Potential Mechanisms For Cd3 Neuronal Functionsupporting
confidence: 78%
“…Syk is also widely expressed in nonhematopoietic cells like fibroblasts, breast cancer cells, colonic carcinoma cells, hepatocytes, neuronal cells, and vascular endothelial cells (Okamura et al, 1999;Coopman et al, 2000;Tsuchida et al, 2000;Tsujimura et al, 2001;Yamada et al, 2001;Yanagi et al, 2001). Originally, Syk was thought to function primarily in signaling of immunoreceptors such as Fc receptor (FcR) and B cell receptor (BCR).…”
mentioning
confidence: 99%
“…U -M, methylated; U, unmethylated; Positive expression is marked by "+"; Reduced or lack of expression is designated by "-" cogene is a mechanism for the gene silencing. Syk is expressed in mammary epithelial cells [1], airway epithelial cells [23], human nasal fibroblasts [24], vascular endothelial cells [25], neuron-like cells [26], hepatocytes [27] and melanocytes [28]. The recent identification of Syk as a potent modulator of tumor epithelial cell growth has generated a need for further exploration of the role of nonreceptor tyrosine kinases in wide cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%